Key indicator tools for shallow slope failure using soil chemical properties signatures and soil color variables - Mohd Shah Irani bin Hasni
Slope failure has become a major concern in Malaysia due to the rapid development and urbanization in the country. It poses severe threats to any highway construction industry, residential areas, natural resources, as well as tourism activities. The extent of damages resulted from this catastrophe can be lessened if a long-term early warning system to predict landslide prone areas is implemented. Thus, this study aimed to develop key indicator tools to predict shallow slope failure based on soil chemical properties and soil color variables. The concentration of each soil properties and chromaticity in both stable and unstable slope soil samples was evaluated using ICP-MS and Remote DRA Cary-50 chroma meter from two different localities that consist of 120 soil samples located along the South Highway (PLUS) and the East Coast Highway (LPT). This study established a marked difference (P<0.0001) of positive correlation between soil properties concentrations and slope failures. Soil texture, total organic carbon (TOC), soil pH, iron oxide and aluminium concentration were the environmental variables that strongly correlated with soil color variables at the studied area. Indicators that could be used to predict shallow slope failure were high value of L* (62), low values of c* (20) and h* (66) with indication between 5 YR to 10 YR, low concentration of iron (53 mgkg-1) and aluminium oxide (37 mgkg-1), low soil total organic carbon (0.5%), low soil cation exchange capacity (3.6 cmol/kg), slightly acidic (pH 4.9), high amount of sand fraction (68 %) and low amount of clay fraction (20%) in soil particles. The reactions and distinctive changes of soil properties between stable and unstable slopes were emphasized as results of highly significant differences were perceived between soil properties, the locations, slope stability and combinations of all interactions. By identifying the key factors controlling slope stability, a greater understanding of how the properties of Oxisols influenced the slope stability in response to interactions with environmental factors would be gained. Besides, the control of such damaging effects would require proper soil conservation strategies such as proper land leveling, afforestation, fallowing, terracing and inclusion of restorative vegetation on the slopes. Therefore, new rating system for shallow slope failure can be developed by implementing these findings as key indicators. The approach of using soil properties to predict the landslide prone areas has never been verified in highway construction industry and also in other industries in Malaysia. This approach is appropriate to be implemented as an indicator to categorize the prospective areas of unstable slopes and simultaneously helps in improving slope stability and safety for future development. Additionally, the mass movement also can be avoided by identifying the areas with the probability of experiencing slope failures at the preliminary phase of development.